Interpreting horizontality. Minor centers, intervention strategies and sustainable development - Bellomo, Mariangela; D’Agostino, Angela (TECHNE - Journal of Technology for Architecture and Environment, 2019)
This paper presents the results of a research carried out within the framework of an Agreement between the Department of Architecture of the University of Naples Federico II and the Municipality of Aquilonia (AV). Inserted in a context of international and national studies aimed at identifying fresh cultural, strategic and operational models for new urban qualities, the research proposes ways of interpreting the city for the definition of intervention criteria also connected to a governance strategy based on the concept of networking. Moving from the specific nature of the Italian hinterland, which can be recognised as a set of horizontal cities within a vertical landscape, the research makes use of the concepts of system and network to investigate the development potential of lesser Italy.